Exploring Work-Family Reconciliation Strategies of Saudi Professional Women: An Applied Study on Female Leadership Professionals in the Government Sector in Riyadh (The International Journal for Scientific Research, 2024)
This study aimed to explore the work-family reconciliation strategies of Saudi professional women. To achieve the study objectives, the qualitative approach was used to collect and analyze data and information by using a semi-structured interview guide with a sample of (15) participants holding leadership positions in the government sector in Riyadh. The results revealed a set of challenges facing Saudi professional women, the most important of which are time, professional, and family burdens, in addition to cultural and social expectations. The study also found that Saudi professional women use a set of strategies to manage the requirements of their work and personal lives, represented by fragmentation, integration, and compromise strategies. Accordingly, the study recommended the need to develop and implement family-friendly policies in the government sector, such as flexible work arrangements and support for caregivers of female employees’ children. The study also recommended conducting more research on the work-family reconciliation experiences of Saudi women in various sectors.
Keywords: Reconciliation; Work; Family; Saudi Professional Women